Ameloblastic fibroma: a case report - Carvalho, Eloisa Muller de; Horikawa, Fernando Kendi; Guimaraes, Letícia; Viveiros, Stephanie Kenig; Lemos, Celso Augusto; Araujo, Juliane Piragine (Clinical and Laboratorial Research in Dentistry, 2015)
Ameloblastic fibroma is a rare benign odontogenic tumor in which both the epithelial and ectomesenchymal components are neoplastic. A 24-year-old male patient was referred to the Stomatology Department presenting with difficulty to chew and swelling in the right posterior region of the mandible. The panoramic radiograph showed a well-circumscribed, unilocular radiolucent lesion with partially radiopaque borders involving first and second unerupted molars. Computed tomography imaging presented a hypodense image with well‑delimited isodense content, bulging cortical bones and absence of rupture. The patient underwent an incisional biopsy. Microscopically, the lesion was composed of many mesenchymal tissue cells in strand form, arranged in cords, islands and nests of odontogenic epithelium; the diagnostic was ameloblastic fibroma. The patient was referred to the hospital for enucleation and curettage of the lesion and extraction of the associated teeth. After 8 months of follow-up, no recurrence was observed. This case emphasizes the importance of differential diagnosis, anatomopathological exam, and both clinical and imaging follow-up, since tumors of this type can recur and progress to malignancy.